Odpowiedzialność świadka składającego fałszywe zeznania w obawie przed grożącą mu odpowiedzialnością karną – glosa do uchwały Sądu Najwyższego z dnia 9 listopada 2021 r., sygn. akt I KZP 5/21 - Dołęgowski, Mikołaj (Studia Prawa Publicznego, 2023)
The commentary pertains to the problem of witnesses giving false testimony in fear of criminal responsibility, which was the subject of the Supreme Court resolution pronounced by 7 Supreme Court judges on 9.11.2021, bearing the signature I KZP 5/21. Due to the fact that it is given the force of a legal principle, the resolution will be of utmost importance for both defense attorneys and prosecutors. The Supreme Court issued the aforementioned resolution in order to normalize its case law regarding Article 233 § 1a of the Polish Penal Code and in doing so the Supreme Courts supports verdict I KZP 19/10. Side notes on the commentary contain a discussion on false testimony, false explanation and the right to defense and the scope of these, in addition to a review of the legal doctrine in this scope. In the commentary, the author attempts to clarify and interpret Article 233 § 1a of Polish Penal Code, due to this point having been omitted in the resolution. The commentary approves the Supreme Court’s stance, mainly because of convincing arguments and conclusions drawn from interpreting the aforementioned article, especially the fact that the article does not extend the range of subjects expressed in Article 233 § 1 of the Polish Penal Code. The resolution in question contradicts the interpretation of the aforementioned provisions as advocated by the National Prosecutor’s Office, yet giving it the force of a legal principle should clarify the interpretative doubts of Article 233 § 1a of the Criminal Code.